ASSOCIATION ASSOCIATION OF SHINE AND LAL INDEX β-THALASSEMIA TRAIT SCREENING RESULTS WITH ANAEMIA AND LOW BIRTH WEIGH - susanti, Susanti; Miftahussurur, Muhammad; Husada, Dominicus; Ningtyas, Woro Setia (Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2023)
Beta thalassemia trait are more likely to have anemia which leading to intrauterine hypoxia and adverse uterine conditions. Adverse intrauterine environment has been shown to have a significant impact on the risk of low birth weight. Therefore, this study aims to investigate association between Shine and Lal index β-thalassemia trait screening results with anaemia and lowbirth weight. A retrospective study design was conducted based on medical records of mothers and their infants born in 2022 at a regional hospital, in East Nusa Tenggara. The inclusion criteria were being live birth, singleton births and gestational age >28 weeks. Mothers didn’t have complete records were excluded from study. Analysis uses chi-square test to evaluate the relationship between dependent and independent variables, This study identified 738 eligible samples. The incidence of suspected β-thalassemia trait according Shine and Lal Index was about 42.5%. There is a significant relationship between Shine and Lal β-thalassemia trait screening results with maternal anaemia and no relationship between Shine and Lal index β-thalassemia trait screening results and LBW